Alternatives to grading student writing - Tchudi, Stephen, 1942-; NCTE Committee on Alternatives to Grading Student Writing (Urbana, Ill. : National Council of Teachers of English, 1997)
A collection of essays that offer alternative options for grading a student's progress as a writer.
Includes bibliographical references.
Adult
Keywords: English language -- Composition and exercises -- Ability testing -- United States; English language -- Composition and exercises -- Study and teaching -- United States -- Evaluation; English language -- Composition and exercises; English language -- Composition and exercises -- Study and teaching -- Evaluation